Biodiesel production by lipases co-immobilized on the functionalized activated carbon. (September 2019) - Lee, Ja Hyun; Lee, Ju Hun; Kim, Dong Sup; Yoo, Hah Young; Park, Chulhwan; Kim, Seung Wook
Abstract: Enzymatic conversion of biodiesel was performed by using co-immobilized lipases. The surface modification of activated carbon (AC) was carried out to improve the stability and reusability of enzyme support. The surface modified AC (ACO: Activated carbon oxide) clearly showed porous and rugged surfaces by scanning electron microscope (SEM) analysis. Subsequently, the Fourier-transform infrared spectroscopy (FT-IR) and X-ray photoelectron spectroscopy (XPS) were carried out to evaluate the generation of functional groups. The highest activity of immobilized lipase was about 10, 360 U/g matrix under pretreatment with co-immobilization method. The activity was maintained about 80% after 20 times of reuse in the batch system. The immobilized lipases were applied to the biodiesel production from different sources of oils such as soybean oil, waste cooking oil and algal oil. The maximum biodiesel conversions from soybean oil, waste cooking oil, and algal oil were found to be 98.5%, 95.7%, and 93.8%, respectively, within 4 h. Graphical abstract: Unlabelled Image Highlights: Lipases were co-immobilized on the functionalized activated carbon oxide. The highest activity of immobilized lipases was about 10, 360 U/g matrix. The activity was maintained about 80% after 20 times of reuse in the batch system. Biodiesel conversions from different oils were >93% within 4 h.